PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT INDOMARCO PRISMATAMA CABANG PANGKALAN JATI DEPOK - Siti Nurbaini Yusuf; Syawaludin Syawaludin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This investigation is designed to empirically examine the magnitude and direction of the influence exerted by Leadership Style and Work Motivation on Employee Performance at PT Indomarco Prismatama, Pangkalan Jati Depok Branch, both in isolated and combined contexts. The study adopts a quantitative paradigm employing an associative research framework. Primary data were obtained through the administration of structured questionnaires to a total of 57 respondents. The analytical procedure encompassed instrument validity and reliability assessments, classical assumption diagnostics, simple and multiple linear regression modeling, correlation and determination coefficient analyses, as well as inferential hypothesis testing using t-tests and F-tests. The empirical findings reveal that the regression constant associated with Employee Performance (Y) is estimated at 4.215. Furthermore, the regression coefficient corresponding to Leadership Style (X₁) is recorded at 0.249, while Work Motivation (X₂) demonstrates a coefficient of 0.658, indicating positive directional effects. The joint association between Leadership Style and Work Motivation with Employee Performance yields a remarkably high correlation coefficient (R) of 0.940, signifying an exceptionally strong relational linkage. Partial hypothesis testing confirms that Leadership Style significantly affects Employee Performance, as reflected by a calculated t-value exceeding the critical threshold (14.852 > 2.005) with a significance probability of 0.000. Similarly, Work Motivation exhibits a statistically significant partial influence, evidenced by a t-value of 19.240 surpassing the t-table value of 2.005 at the same significance level. Simultaneous testing further substantiates the combined effect of both independent variables on performance outcomes, as indicated by an F-statistic of 203.754 exceeding the critical value of 3.17. The coefficient of determination, amounting to 88.3%, demonstrates that the majority of variance in Employee Performance is accounted for by Leadership Style and Work Motivation, while the remaining 11.7% is attributable to extraneous variables beyond the scope of this study. Keywords: Leadership Style; Work Motivation; Employee Performance